2019
DOI: 10.3847/2041-8213/ab4cf3
|View full text |Cite
|
Sign up to set email alerts
|

Round-trip Slipping Motion of the Circular Flare Ribbon Evidenced in a Fan-spine Jet

Abstract: A solar jet on 2014 July 31, which was accompanied by a GOES C1.3 flare and a mini-filament eruption at the jet base, was studied by using observations taken by the New Vacuum Solar Telescope and the Solar Dynamic Observatory. Magnetic field extrapolation revealed that the jet was confined in a fan-spine magnetic system that hosts a null point at the height of about 9 Mm from the solar surface. An inner flare ribbon surrounded by an outer circular ribbon and a remote ribbon were observed to be associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
4
33
0
1
Order By: Relevance
“…They found that the initiation of the jet is due to the magnetic reconnection near a set of two 3D magnetic nullpoints, and the jet itself evolves from a flux rope near the nullpoints through changing the flux rope’s magnetic field lines from an anchored to an open topology. In addition, the generation of flare ribbons is found to be attributed to reconnections at a 3D nullpoint and a quasi-separatrix layer, consistent with a previous data-constrained simulation of circular flares [50] and the observations of confined fan–spine jets [55].…”
Section: Physical Interpretation and Modellingsupporting
confidence: 88%
See 3 more Smart Citations
“…They found that the initiation of the jet is due to the magnetic reconnection near a set of two 3D magnetic nullpoints, and the jet itself evolves from a flux rope near the nullpoints through changing the flux rope’s magnetic field lines from an anchored to an open topology. In addition, the generation of flare ribbons is found to be attributed to reconnections at a 3D nullpoint and a quasi-separatrix layer, consistent with a previous data-constrained simulation of circular flares [50] and the observations of confined fan–spine jets [55].…”
Section: Physical Interpretation and Modellingsupporting
confidence: 88%
“…By contrast, a two-sided-loop jet appears as a pair of plasma beams ejecting in opposite directions from the eruption source region [44][45][46][47][48][49]. Recently, high-resolution observations combined with extrapolated three-dimensional (3D) coronal magnetic fields revealed the fan-spine topology magnetic system of straight anemone jets [50], which consists of a coronal nullpoint, a dome-like fan that represents the [51][52][53][54][55][56][57][58][59][60]. A fan-spine topology often arises when a parasitic magnetic polarity emerges (or carries) into a pre-existing magnetic field region with opposite polarity, and a jet occurring within it can lead to three flare ribbons as a result of the low-altitude impact of the particle beams accelerated through the nullpoint magnetic reconnection; namely, an inner bright patch surrounded by a circular ribbon relevant to the inner spine and the dome-like fan structure, and a remote elongated bright ribbon associated with the outer spine.…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ñïàëàõîâ³ ïåòë³ êîâçàþòü ó ïðîòèëåaeíèõ íàïðÿìêàõ äî ê³í ö³â ñòð³÷îê. Ö³êàâèé ôàêò êîâçàííÿ ó ñòð³÷ö³ ñïàëàõó áàëà C1.3 31 ëèïíÿ 2014 ðîêó ñïî÷àòêó íà ï³âí³÷, à ïîò³ì íà ï³âäåíü âèÿâëåíî â ðîáîò³ [41]. Ó ðîáîò³ [19] ïîâ³äîìëÿºòüñÿ ïðî ñïîñòåðåaeåííÿ òðè âàëîãî âåëèêîìàñøòàáíîãî êîâçíîãî ïåðåç'ºäíàííÿ ó ñïàëàõó M6.5 â àê -òèâí³é îáëàñò³ NOAA 12371.…”
Section: îáãîâîðåííßunclassified